Deep disentangling learning for real-world image enlightening and restoration - Chan, Yi Xuan (Nanyang Technological University, 2022)
Shadow removal is a vital image processing operation that can enlighten the illumination of shadow regions in an image. This application can elevate the accuracy and robustness of high-level computer vision tasks especially those which are heavily deep learning (DL) based (e.g., object detection, person surveillance, and vehicle tracking). Implementation of shadow removal on image or video data can mitigate the risk of unexpected fallouts in computer vision algorithms.